Anatomical study of the arterial blood supply of dog pancreas - Mostafa, Samyan Luqman; Mohammed, Yahya Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2020)
This research was carried out to study the arterial blood vessels of the pancreas in dogs by using latex injection. The six adult male and female dogs were collected from Sumel town -Duhok governorate, Kurdistan region-Iraq. Our results exhibited that the left lobe of dog pancreas was supplied by pancreatic branches originated from celiac, splenic and gastroduodenal arteries. The right lobe was equipped by pancreatic branches aroused from both cranial and caudal pancreaticoduodenal arteries which were anastomosed within the gland. In addition to supply the right lobe, the cranial pancreaticoduodenal artery was also supplied the body of pancreas. The present study recorded a significant variation in the origin, number and distribution of most aforementioned arteries. Therefore, the anatomists and surgeons should take this into account during dissected of cadavers or performed the surgical operations.
Keywords: Pancreas; Dog; Arterial; vessels Latex